Orbital-Driven Rashba Effect in a Binary Honeycomb Monolayer AgTe - Unzelmann, Maximilian; Bentmann, Hendrik; Eck, Philipp; Kißlinger, Tilman; Geldiyev, Begmuhammet; Rieger, Janek; Moser, Simon; Vidal, Raphael C.; Kissner, Katharina; Hammer, Lutz; Schneider, M. Alexander; Fauster, Thomas; et al. (Physical Review Letters, 2020)
The Rashba effect is fundamental to the physics of two-dimensional electron systems and underlies a variety of spintronic phenomena. It has been proposed that the formation of Rashba-type spin splittings originates microscopically from the existence of orbital angular momentum (OAM) in the Bloch wave functions. Here, we present detailed experimental evidence for this OAM-based origin of the Rashba effect by angle-resolved photoemission (ARPES) and two-photon photoemission experiments for a monolayer AgTe on Ag(111). Using quantitative low-energy electron diffraction analysis, we determine the structural parameters and the stacking of the honeycomb overlayer with picometer precision. Based on an orbitalsymmetry analysis in ARPES and supported by first-principles calculations, we unequivocally relate the presence and absence of Rashba-type spin splittings in different bands of AgTe to the existence of OAM.
CRIS-Team WoS Importer:2020-05-15